STUDI PARAMETRIK DEFORMASI TORSI LANTAI BANGUNAN ASIMETRIS SEBIDANG DIPENGARUHI OLEH GEMPA PULSE DAN TANPA PULSE - Ade Faisal; Gamal Halim (Politeknik Negeri Lhokseumawe, 2017)
Earthquake resistant building must be designed with a proper plan configuration. Although the regular and symmetrical building plans have been known to have a good behaviour under earthquake loads, but the facts have demonstrated that many asymmetrical plan buildings are built for the architectural reasons. Irregular plan buildings cause mass distribution, stiffness, and strength asymmetries which in turn produce the eccentricity to the centre of mass. In this research, the asymmetrical buildings are simulated under earthquake ground motion containing pulse. The study aims to evaluate the drift and floor rotations that occur in the asymmetrical buildings. The results indicate that the difference in drift of symmetrical and asymmetrical buildings reach 8% to 20%. The rotation occurred on the rigid side (high stiffness side) is smaller than the flexible side (low stiffness side). The difference in eccentricity affects clearly the inelastic floor rotation.Keywords: Eccentricity Stiffness, Pulse Ground Motion, Floor Rotation